IDENTIFIKASI PENGGUNAAN LAHAN DI HUTAN LINDUNG KEBUN KOPI DESA NUPABOMBA KECAMATAN TANANTOVEA KABUPATEN DONGGALA - Witno, Witno; Akhbar, Akhbar; Arianingsih, Ida (Warta Rimba, 2014)
Kebon Kopi protected forest Â is located in the area of Nupabomba village, Tanantovea district, Donggala regency, Central Sulawesi Province with total area is 546.78 ha.Â  From those lands, there is a significant change of land function. So that the broad of its lands have been changed. It can be proven by the plenty of land use on it. Protected forest is a conservation forest which has a main function as protection of life support systems like water, prevent flooding, control erotion and maintain soil fertility. Â This research was aimed to identify the use of land at Kebon Kopi protected forest Nupabomba Village, Tanantovea district, Donggala regency. This research was conducted area at Kebon Kopi protected forest in Nupabomba Village, Donggala regency. The method used in this research was Classification Supervised. Classification Supervised is a process of clarificating or grouping the pixels based on the examples of land Â which its of type object and spectral value are known on the image by using Citra Alos year 2009 as its materials and Arc.Gis 10.0 as its operational tool. The research was conducted at Nupabomba village, Tanantovea district, Donggala regency. The result of the research shows that the total forest area is 546.78 ha, which consists of primary forest which has a more dominant region with the area is ââ467.1 ha (85.42%) and secondary forest is ââ68.63 ha (12.55%). Furthermore, the closure of land for plantations covering 8.26 ha (1.51%), the settlement has is 1.55 ha (0.28%), and shrubs covering 0.64 ha (0.11%). And water body area is 0.6 ha (0.10%). Â  Keywords: Identification, Land Use, Citra Alos year 2009, Kebon Kopi Protected Forest. Â